« A very Great Briton » : Construire la mémoire postcoloniale d’Ignatius Sancho dans Sancho: An Act of Remembrance (2011) et The Secret Diaries of Charles Ignatius Sancho (2022) de Paterson Joseph - Vanessa Alayrac-Fielding (XVII-XVIII)
This paper examines the ways in which Ignatius Sancho’s life and legacy have been forgotten and remembered in Britain since the end of the eighteenth century. It argues that the paucity of archival material makes way for innovative methods to memorialise Sancho’s unique social trajectory and explores the contribution of literature to a renewed historiography of Afro-Caribbean diasporic identity in Britain through the study of the play Sancho: An Act of Remembrance (2011) and the novel The Secret Diaries of Charles Ignatius Sancho (2022) by Paterson Joseph. In examining the poetic and historical recreation of Sancho’s story, attention will be paid to the use of performance, intertextuality and critical fabulation.